Effects of slackline training during active breaks and free-time activities break at school on children's attention: a comparison of two-intervention methods - Paula Plaza-Arancibia; Oscar Achiardi Tapia; Julio Brugnara Mello (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Purpose: To describe the effects of two interventions, regular Physical Education classes plus free active break times and school Physical Education plus Slackline classes during free time, on the attention of schoolchildren. Methods: This is a quasi-experimental study with a quantitative approach. Two groups participated in the interventions: body balance training (Slackline group) (n: 10; age: 7,8±1,93) and free-time activities break (FTA group) (n: 10; age: 7,8±1,22). Attention was assessed using the D-2 test. Repeated measures ANOVA was used. The magnitude of the effect size was estimated by the partial squared eta - η2p. Results: When we analyzed the interactions between time*group, it was not possible to find significant changes attributed to the specificities of the one intervention group, with most results having a medium effect size (η2p≥ 0.06 ≤ 0.25). The results of the paired analysis confirmed that both groups improved the results over time, but the slackline group showed changes with a slightly greater magnitude. Conclusions: Our results demonstrate that in free time, both free physical activities and body balance training are effective for children's attention. However, pairwise analysis revealed that both groups demonstrated improvements over time, with the slackline group showing slightly greater changes in magnitude.